Amblyceps vayavy, a new catfish from the northern part of the Western Ghats, India (Teleostei: Amblycipitidae) - Vijayakrishnan, Balaji; Thackeray, Tejas; Shirke, Abhishek (Zootaxa, 2026)
Amblyceps vayavy, a new species of amblycipitid catfish, is described from the northern part of the Western Ghats Hotspot, India. The new species can be distinguished from all congeners in having the following combination of characters: forked caudal fin, adipose-fin separate from dorsal procurrent part of the caudal fin, centrally projecting hooks on proximal lepidotrichia of median caudal-fin rays absent, incomplete lateral line, lower jaw longer than upper, anal-fin base 15.3–15.9% SL, body depth at anus 14.7–15.3% SL, and adipose-fin base length 21.8–22.3% SL.